Identity Paradoxes: How Senior Managers and Employees Negotiate Similarity and Distinctiveness Tensions over Time. Issue 3 (April 2017) - Cuganesan, Suresh
Employee identity is shaped by a need to feel similarity to, as well as distinctiveness from, others in organizations. While this paradoxical tension is important we know little about how it is managed over time, especially when senior managers prioritize one element of the paradox over the other. Consequently I investigate how senior managers and employees negotiate the similarity–distinctiveness identity paradox over time, doing so through a longitudinal case study of a police organization undergoing change. The study contributes to prior paradox literature in two significant ways. First, it reveals how senior managers and employees negotiate tensions in employee identity between similarity and distinctiveness as an emergent and cyclical process of identity regulation and heterogeneous identity work. This shows how the balance between similarity and distinctiveness is both elusive to achieve for all organizational participants and difficult to sustain over time. Second, it highlights how defensive approaches to identity paradox may lead to positive outcomes, with this contingent on organizational participants' ability to make strong claims about the importance of the paradox element they favour for the organization's future.